1990
DOI: 10.1007/bf00025277
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-acetic acid concentration and ethylene evolution during early fruit development in peach

Abstract: Ethylene evolution was measured from greenhouse-grown 'Jerseyglo' peach fruits beginning 29 days after anthesis. Indole-3-acetic acid (IAA) levels were measured in the pericarp and seed tissues of individual fruits on a single shoot when variable ethylene evolution was noted . Despite hand-pollinating all flowers on the same day, variability within the shoot existed in fruit fresh weight, IAA levels, and ethylene evolution . Seed IAA concentration increased as fruit and seed fresh weight increased and ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
6

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
3
0
6
Order By: Relevance
“…Ethylene production in S1 is perhaps needed for regulating the abundant cell division characterizing early fruit growth. Results similar to ours have been reported in peach (Miller and Walsh, 1990;Tonutti et al, 1997). However, due to the small fruit size (recently fertilized ovary), we were unable to determine the part of the fruit in S1 that was directly involved in this notable production of ethylene.…”
Section: Discussionsupporting
confidence: 86%
“…Ethylene production in S1 is perhaps needed for regulating the abundant cell division characterizing early fruit growth. Results similar to ours have been reported in peach (Miller and Walsh, 1990;Tonutti et al, 1997). However, due to the small fruit size (recently fertilized ovary), we were unable to determine the part of the fruit in S1 that was directly involved in this notable production of ethylene.…”
Section: Discussionsupporting
confidence: 86%
“…Actually, an increase of IAA in the seeds (on a per seed or a fresh weight basis) coincided with an increase of seed dry weight between weeks 4 to 6 AFP. The coincidence of IAA increase and seed growth between early to mid-developmental stages is also found in many angiosperms, such as Sechium edule (Di Gregorio et al 1995), peach (Miller and Walsh 1990) and tomato (Hocher et al 1992). At the late maturation stage, the decrease in embryo IAA may reflect slower embryo growth.…”
Section: Discussionmentioning
confidence: 74%
“…Pollination and fertilization are the main predictors of fruit growth during these early stages and it has been suggested that seed-produced auxin is involved in fruit set and development (Weaver, 1972). This view is supported by reports showing that IAA content in the seeds is higher than that in the mesocarp of strawberry (Fragaria ×ananassa Duchesne) (Nitsch, 1950), peach [Prunus persica L. Batsch (Peach Group)] (Miller and Walsh, 1990) and tomato (Lycoperisicon esculentum Mill.) (Hocher et al, 1992).…”
Section: Methodsmentioning
confidence: 55%